A Moderated Mediation Model of the Relationship Between Depression and Internet Addiction: Mediation by Refusal Self-Efficacy of Internet Use and Moderation by Online and Real-Life Social Support. - Chen, Kuan-Chu; Liu, Sihan; Lin, Min-Pei; Lee, Yueh-Ting; Wu, Jo Yung-Wei; Lin, Chun-An; You, Jianing (International Journal of Mental Health & Addiction, 2024)
Based on the theoretical frameworks of the theory of triadic influence (TTI) and the buffering hypothesis, this study was designed to examine whether the relationship between depression and Internet addiction (IA) was mediated by refusal self-efficacy of Internet use and whether real-life and online social support moderated the effect of depression on refusal self-efficacy of Internet use among adolescents. A sample of 1127 junior high school students from Taiwan completed a self-report battery that included measures of depression, online social support, real-life social support, refusal self-efficacy of Internet use, and IA. The prevalence of depression and IA are 44.6% and 23% respectively. Structural equation modeling and bootstrapping analysis results showed that IA was significantly and positively predicted by depression and mediated by refusal self-efficacy of Internet use. Moreover, the results of the moderated mediation analyses revealed that real-life and online social support played a moderating role in the indirect effects of depression on IA through refusal self-efficacy of Internet use, such that indirect effects were attenuated by an increase of online social support, and in contrast, those effects promoted the increase of real-life social support. The results supported the TTI framework and the buffering hypothesis. The moderated mediating role of online and real-life social support and refusal of self-efficacy of Internet use in the relationship between depression and IA were discussed.